The Relationship between Focal Surfaces and Surfaces at a Constant Distance from the Edge of Regression on a Surface - Semra Yurttancikmaz; Omer Tarakci (Advances in Mathematical Physics)
We investigate the relationship between focal surfaces and surfaces at a constant distance from the edge of regression on a surface. We show that focal surfaces F1 and F2 of the surface M can be obtained by means of some special surfaces at a constant distance from the edge of regression on the surface M.